ANALYSIS OF HEATING PECULIARITIES OF FORMING OF UNINTERRUPTEDLY-CASTED WIRE SLUGS - E. I. Marukovich; A. M. Branovitskij; Ju. A. Lebedinskij; V. A. Dementjev (Литьë и металлургия)
The heating peculiarities of forming of wire slugs of precious alloys at continuous casting in graphite crystallizer are investigated